The antiarrhythmic activity comparative study of Lappaconitine hydrobromide and LMG-124 on the model of aconitine arrhythmia - V. N. Stolyaruk; I. B. Tsorin; M. B. Vititnova; T. D. Nikiforova; Yu. I. Murinov; M. S. Yunusov; S. A. Kryzhanovskii (LLC "Publisher OKI", 2017)
Two models of the aconitin-induced cardiac arrhythmias were used to compare the antiarrhythmic and antifibrillatory activity of the reference drug Lappaconitine hydrobromide and the LMG-124 compound. It is shown that both compounds have antiarrhythmic action. At the same time, the compound LMG-124 realizes its antiarrhythmic effect in a significantly lower dose. In this case, the compound LMG-124 shows a pronounced antifibrillatory activity, in contrast to the reference drug Lappaconitine hydrobromide, which in the studied dose does not exhibit similar activity.